Probiotic Lactobacillus reuteri Prevents Postantibiotic Bone Loss by Reducing Intestinal Dysbiosis and Preventing Barrier Disruption. (28th January 2019) - Schepper, Jonathan D; Collins, Fraser L.; Rios‐Arce, Naiomy Deliz; Raehtz, Sandi; Schaefer, Laura; Gardinier, Joseph D; Britton, Robert A.; Parameswaran, Narayanan; McCabe, Laura R
ABSTRACT: Antibiotic treatment, commonly prescribed for bacterial infections, depletes and subsequently causes long‐term alterations in intestinal microbiota composition. Knowing the importance of the microbiome in the regulation of bone density, we investigated the effect of postantibiotic treatment on gut and bone health. Intestinal microbiome repopulation at 4‐weeks postantibiotic treatment resulted in an increase in the Firmicutes:Bacteroidetes ratio, increased intestinal permeability, and notably reduced femoral trabecular bone volume (approximately 30%, p < 0.01). Treatment with a mucus supplement (a high‐molecular‐weight polymer, MDY‐1001 [MDY]) prevented the postantibiotic‐induced barrier break as well as bone loss, indicating a mechanistic link between increased intestinal permeability and bone loss. A link between the microbiome composition and bone density was demonstrated by supplementing the mice with probiotic bacteria. Specifically, Lactobacillus reuteri, but not Lactobacillus rhamnosus GG or nonpathogenic Escherichia coli, reduced the postantibiotic elevation of the Firmicutes : Bacteroidetes ratio and prevented femoral and vertebral trabecular bone loss. Consistent with causing bone loss, postantibiotic‐induced dysbiosis decreased osteoblast and increased osteoclast activities, changes that were prevented by both L. reuteri and MDY. These data underscore the importance of microbial dysbiosis in the regulation of intestinal permeability and bone health, as well as identify L. reuteri and MDY as novel therapies for preventing these adverse effects. © 2018 American Society for Bone and Mineral Research.